Evaluation of Horizontal Alignment Design Using AutoCAD® CIVIL 3D: Case Study of Majalengka-Sumedang (STA 0+000-STA 0+713) - Damar Gusti Astapati; Jody Martin Ginting (LEADER: Civil Engineering and Architecture Journal, 2024)
Road infrastructure is crucial for development, enhancing access to transportation and fostering regional and national growth. Indonesia's mountainous terrain, shaped by tectonic plate activity, creates road construction and maintenance challenges. An example is the Majalengka-Sumedang Road in West Java, which has uneven surfaces that frequently cause traffic accidents. Effective road design must consider cross-sectional features, visibility, vehicle stability, driver comfort, traffic dynamics, and financial aspects. Professionals use AutoCAD® Civil 3D, a BIM software, for precise highway planning, essential for safe, economical, and efficient roads. Data collection is a key initial step in addressing these challenges. For instance, the Majalengka-Sumedang Road, especially around kilometer five, is being evaluated following the 2021 Road Geometric Design Guidelines. These guidelines dictate specific design criteria, including calculations for horizontal alignment factors like Straight Section Length, Bend Radius, Bend Length, and Transition Curve Length. The road section from STA 0+000.00 to STA 0+713, with a 10-25% slope, requires thorough excavation and stockpiling to meet design specifications. Evaluations show this road is a hill type, particularly at mile 5, with five horizontal alignments assessed at a 60 km/h design speed, ensuring compliance with design standards.